National Identity and Democracy Ratings - Bush, Sarah Sunn; Platas, Melina R. (SAGE Publications, 2025)
Global performance indicators, such as democracy ratings, are influential tools of global governance and can have a direct bearing on foreign policy, aid, and investment. Many of these indicators rely on expert assessments. Although expert assessments are generally understood to be objective, this article suggests raters’ identities may shape their assessments. It specifically examines how national identity shapes democracy ratings. Two data sources—an original survey of experts on Uganda and the Varieties of Democracy Institute—reveal significant differences in the ratings provided by national and non-national experts. In most cases, ratings by nationals are more positive. This article explores three potential reasons for the difference, finding some support for each: national differences in information access and consumption, national differences in conceptions of democracy, and in-group–out-group bias. The findings have implications for our understanding of global performance indicators, which are overwhelmingly a product of Global North organizations.